PENGARUH UKURAN PERUSAHAAN PROFITABILITAS DAN SOLVABILITAS TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN INFRASTRUKTUR YANG TERDAFTAR PADA BEI TAHUN 2021-2023 - Salma Nur Afi; Sri Laksmi Pardanawati; LMS Kristiyanti (Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the effect of company size profitability and solvency onthe timeliness of financial reporting in infrastructure companies listed on the IDX in 2021-2023. The independent variables in this study consist of company size, profitability and solvency while the dependent variable is timeliness. A quantitative approach is used with multiple linear regression analysis methods based on secondary data in the form of company financial reports. The research sample consisted of 29 companies selected through purposive sampling technique based on certain criteria. The results showed that company size has a significant negative effect. Conversely, profitability and solvency have no effect on timeliness